Studi Eksperimental Variasi Pretension Sambungan Baut Baja Tipe Slip Critical - Ardison Gutama; Alex Kurniawandy; Warman Fatra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
On the bridge connection type found using high strength bolts with the type of slip-critical connections. In the installation of high quality bolt connection types is conducted pretension with using torque wrench or using manual tool by turn of nut. This study aims to determine tensile strength and failure behavior of the critical slip-type connection by varying the value of pretension on single bolt locking connection with different methods. Pretension variation used 90 Tb, 100 Tb and 110 Tb for torque wrench and 2/3, 3/6 and 4/6 rounds for manual tools of pretension respectively.Tensile test performed on each variation and variation locking method. The results showed the tensile strength values at the both locking methods are same and the failure behavior result are the bolt fail in shear and plate changes into an oval shape.Keywords: Pretension, Connection slip critical, high tensile bolt, tensile strength of connection.